A modification of the CABARET scheme for resolving the sound points in gas flows - Danilin, A.V.; Solovjev, A.V. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2020)
An explicit numerical algorithm for resolving the sound points in the framework of the CABARET scheme is proposed. The sound points are characterized by a sign change in at least one of characteristic velocities. The flows in mesh nodes corresponding to sound points are calculated by solving the Riemann problem. This approach is successfully tested on a problem with sound transitions on rarefaction waves, on a problem with two diverging supersonic flows, and on a problem with supersonic flow over a forward facing step.